Integrated View on Theory and Practice of Social Work – An Answer to the Human Challenge of the 21st Century - Jucevičienė, Palmira (Acta Paedagogica Vilnensia, 2001)
This paper aims at revealing an intricate essence of social work, determined by the qualities of developing information and knowledge society, and attempts to detect a theory to ground this essence il1 a most general way. It has been determined that a proportion of two action theories, the espoused and action-in-use theories, reveals such an integrated view to the theory and practice of social work. This proportion can be empowered by the usage of a double-loop learning which enables changing not only action strategies, but also their value basis. This is the only means to secure the improvement of theories-il1-use which determines a person's ability to solve his or her problems. To implement such an integrated view towards the theory and practice of social work, social work professionals are required to possess a broad multidisciplinary training, open mind, critical thinking, and reflection-based action research skills. Therefore, such professionals have to undergo modern action-based university studies which encompass broad theoretical education and practical work.
Keywords: Knowledge society; higher education; vocational education; social work theory.